The Tradition of The Batak Toba Tribe Marriage in The Novel “Mangalua” By Idris Pasaribu - Ayumi, Alfi Yalda; Supriyanto, Teguh; Doyin, Mukh (Universitas Negeri Semarang, 2022)
Mangalua (elopement) carried out by a pair of teenagers to realize a marriage that does not get the blessing of both families. Mangalua's activities will damage the name of the women's family because Batak sons forcibly flee their daughters. Research purposes This study aims to find and analyze the settlement of elopement and to find the factors causing the occurrence of elopement contained in the novel Mangaula by Idris Pasaribu. The data collection method used is a method with a first-level semiotic reading technique, namely by heuristic reading with a sociological research approach to Gramsci's literature in Williams. The results of the study found the completion of elopement contained in the novel Mangalua by Idris Pasaribu, namely with several stages including: Martandang, Mangalehon Tanda, Marhusip, Marhata Sinamot and Manjala Sinamot, Maningkir Lobu, Martonggo Raja, Marriage Ceremony. Furthermore, to find the factors that cause the occurrence of the Toba Batak elopement in the novel Mangalua by Idris Pasaribu, among others, because they did not get the approval or blessing of the women, namely the Siboru Anting family. The benefit of the research is as an addition to knowledge to the reader regarding the completion of the traditional Mangalua (elopement) activities in the Toba Batak tribal community which must be preserved.